2021
DOI: 10.3390/ijerph18020775
|View full text |Cite
|
Sign up to set email alerts
|

Association between Dyslipidemia and Mercury Exposure in Adults

Abstract: Background—Dyslipidemia is one of the prominent risk factors for cardiovascular disease, which is the leading cause of death worldwide. Dyslipidemia has various causes, including metabolic capacity, genetic problems, physical inactivity, and dietary habits. This study aimed to determine the association between dyslipidemia and exposure to heavy metals in adults. Methods—Using data from the seventh Korean National Health and Nutrition Examination Survey (2016–2017), 5345 participants aged ≥20 years who were tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…thus remain a formidable task that calls for effective countermeasures and intense efforts. Over the past few decades, evidence has reported that the risk of dyslipidemia may be increased by environmental toxicants, including Pb, Hg, and Se(Hx, Yu, Bx, & Yh, 2020; Joachim et al, 2008;Kang et al, 2021b). In our study, a similar nding was observed that four single metals, PB, Total Hg, Mn and Se, were signi cantly associated with an increased risk of dyslipidemia.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…thus remain a formidable task that calls for effective countermeasures and intense efforts. Over the past few decades, evidence has reported that the risk of dyslipidemia may be increased by environmental toxicants, including Pb, Hg, and Se(Hx, Yu, Bx, & Yh, 2020; Joachim et al, 2008;Kang et al, 2021b). In our study, a similar nding was observed that four single metals, PB, Total Hg, Mn and Se, were signi cantly associated with an increased risk of dyslipidemia.…”
Section: Discussionsupporting
confidence: 84%
“…Metals, which ll the environment and are di cult to degrade, can be easily absorbed by people through dermal contact, assimilation of food chain or respiratory tract from water, air, and soil, accumulating in the human body over time (Fu & Xi, 2020). In daily life, people are often exposed to metals coming from industrial waste gases, wastewater, contaminated soil, drinking water, or food (Kang, Shin, & Kim, 2021b). For example, consuming raw meat and smoking(whether active or passive smoking) are two common examples of taking in metals into the human body, which, put more directly, is metal pollution, a very serious prevalent environmental threat.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of combined metal exposure on dyslipidemia was not observed in a cross-sectional study from the United States [ 54 ]. However, a study of dyslipidemia in adults found significant between-group differences in multiple heavy metal exposures in females [ 8 ]. There are very few studies on the overall effect of metal mixtures on dyslipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…The heavy metals chromium (Cr), iron (Fe), zinc (Zn), arsenic (As), strontium (Sr), cadmium (Cd), and lead (Pb) may be associated with dyslipidemia occurrence [ 3 , 7 ]. People are often exposed to heavy metals in their daily lives through exposure to industrial waste gases, wastewater, contaminated soil, drinking water, or food [ 8 ]. Pollution is caused by metal mines, smelting, and others.…”
Section: Introductionmentioning
confidence: 99%
“…A positive correlation has been reported between exposure to Hg and blood pressure measures during childhood [ 27 ]. There is also a positive association between high levels of Hg and dyslipidemia in adults [ 28 ]. Several studies on the effect of Hg on liver function found that liver enzymes increased significantly with Hg exposure [ 29 ].…”
Section: Impact Of Hms On Human Healthmentioning
confidence: 99%